Drug use in acute otitis media: a prospective study at a tertiary care teaching hospital - Pandya, Rushi N.; Patel, Maulik M.; Patel, Varsha J. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Drug use study identifies the problems that arise from prescription and highlights the current approaches to the rational use of drugs. The objective of the study was to assess drug use pattern in patients diagnosed of acute otitis media in tertiary care teaching hospital. Methods: This prospective observational study was carried in the Otorhinolaryngology department of a tertiary care teaching hospital over a period of twelve months. The data collected for patients with acute otitis media included the patient’s demographic details and the drugs prescribed. Data were analysed for drug use pattern and cost per prescription and assessment of rationality of prescription. Results: Total 153 patients were analysed, 100 (65.35%) belonged to male patients and 53 (34.65%) belonged to female patients. Children less than 2years age were the most diagnosed with AOM 47.71%, the major diagnostic symptoms were earache (58.16%) and fever (54.90%) and signs were congestion (52.94%) and discharge (43.13%). In a total 153 prescriptions (469 drugs), 33.68% were antimicrobials, followed by mineral supplements (23.67%). Average number of drugs per prescription was found to be 3.0. Most common antibiotic prescribed was amoxicillin (with or without clavulanate) in 142 (92.81%) patients. Paracetamol alone or in fixed dose combination with antihistaminics were prescribed in 131 patients. Average cost per prescription was 87.74(±35.67) Indian rupees. Seventeen (11.11%) prescriptions were rational in all the aspects based on standard guidelines. Conclusions: The present study showed that paracetamol and amoxicillin with or without clavulanate were mostly commonly prescribed in children with AOM. Irrational prescribing was seen in maximum number of cases.